Potensi Silvofishery Sebagai Blue Carbon Reservoir dan Sumber Pendapatan Masyarakat di Desa Sawah Luhur, Banten dalam Mitigasi Perubahan Iklim : The potential of silvofishery as a blue carbon reservoir and source of community income in Sawah Luhur Village, Banten in climate change mitigation - Adni, Salsa Fauziyyah; Fatimah, Gintan; Saputri, Hanum Resti; Rahmadhani, Khorina; Hartoyo, Adisti Permatasari Putri (Jurnal Silva Tropika, 2024)
ABSTRACT Sawah Luhur Village, Banten community has a fishery cultivation livelihood using silvofishery system. Silvofishery systems have high potential in storing carbon stocks in climate change mitigation. However, baseline data related to blue carbon reservoirs and sources of community income from the silvofishery system are still limited. This research aims to estimate carbon stocks (blue carbon reservoir) and calculate community income in the silvofishery system in Sawah Luhur Village, Banten. The method used was an allometric approach to estimate the amount of potential carbon stocks, analysis of vegetation on 100 plots, and interviews with the community. Biomass and carbon stock data were collected using non-destructive sampling on 20 transects perpendicular to the shoreline with 5 square plots measuring 10 m x 10 m for each transect line. The silvofishery economic assessment in Sawah Luhur Village uses the total economic value approach which is calculated from the sum of the direct benefits of the presence of mangrove resources. It is estimated that the average carbon stock stored in 10 ponds at the stake and pole level yields 94.67 tons/ha. The silvofishery system in fish farming ponds is dominated by milkfish with yields from each pond ranging from IDR 1,500,000 to IDR 7,000,000 per harvest (mangrove and fish components).   Keywords: biomass, carbon, mangrove, Rhizophora mucronata   ABSTRAK Masyarakat di Desa Sawah Luhur, Banten memiliki mata pencaharian budidaya perikanan dengan sistem silvofishery. Sistem silvofishery memiliki potensi tinggi dalam menyimpan cadangan karbon dalam mitigasi perubahan iklim. Akan tetapi, baseline data terkait simpanan cadangan karbon (blue carbon reservoir) dan sumber pendapatan masyarakat dari sistem silvofishery masih terbatas. Tujuan riset ini adalah untuk mengestimasi simpanan karbon (blue carbon reservoir) dan menghitung pendapatan masyarakat pada sistem silvofishery di Desa Sawah Luhur, Banten. Metode yang digunakan dalam mengestimasi cadangan karbon adalah pendekatan allometrik dengan membuat 100 plot contoh dan mengidentifikasi jenis pada tingkat pancang dan pohon. Wawancara dilakukan kepada masyarakat terkait pendapatan dari silvofishery. Hasil riset menunjukkan bahwa cadangan karbon tersimpan pada tingkat pancang dan pohon sebesar 94,67 ton/ha. Jenis yang dominan adalah Rhizophora mucronata dan Avicennia marina, sedangkan jenis tambak yang banyak dibudidayakan adalah ikan bandeng (Chanos chanos). Pendapatan masyarakat dari pengembangan sistem silvofishery berkisar antara Rp 6.000.000,- sampai Rp 24.000.000,- per tahun. Sistem silvofishery berpotensi tinggi dalam menyimpan cadangan karbon dan meningkatkan pendapatan masyarakat.   Katakunci: biomassa, karbon, mangrove, Rhizophora mucronata